Penerapan SAK ETAP Pada Koperasi Aktif di Jawa Barat Sebagai Acuan Pembuatan Aplikasi Akuntansi Koperasi Berbasis Android - Toufiq Agung Pratomo Sugito Putra; Muhamad Ardi Nupi Hasyim (Coopetition : Jurnal Ilmiah Manajemen, 2021)
The development of accounting information technology has actually been going on for a long time. This is because the use of technology in accounting can save time and costs and the use of technology in accounting is considered very efficient. In order to provide accounting information, an information system known as the Accounting Information System (SIA) was created. A good accounting information system requires a good system design too. At Cooperative, data processing is still done manually using Microsoft Excel, which makes this cooperative vulnerable to recording errors. Apart from errors in recording, delays in delivering information can also occur due to ineffective recording. Therefore, this cooperative needs to use a cooperative accounting information system. Which this system will later be able to assist the cooperative in carrying out the existing transaction process in the cooperative effectively and efficiently and well computerized. Based on this, this study aims to determine the financial reporting accounting information system that has been implemented by the Cooperative and to design an application-based savings and loan cooperative financial reporting accounting information system in accordance with the needs of Cooperative. This study used qualitative and experimental methods, while the application design method used was a waterfall. The system development method used in this research is Netbeans IDE with Java programming language and Mysql as database storage and iReport to design financial statements.The results obtained from the analysis and design carried out is an accounting information system design that is able to support the operational needs of Cooperative. The superiority of the resulting system is that there is a treasurer who specifically manages the finances of the Cooperative so that the process of recording financial reporting runs effectively and efficiently which has been designed according to the needs of Cooperative